4
$\begingroup$

Let $R,S$ be rings and $\varphi : R\to S$ be a ring homomorphism. Verify that

  1. $\varphi(na) = n\varphi(a)$ for all $n\in\mathbb Z$ and $a\in R$.
  2. $\varphi(a^n) = (\varphi(a))^n$ for all $n\in\mathbb Z^+$ and all $a\in R$.
  3. If $A$ is a subring of $R$, then $\varphi(A) = \{\varphi(a):a\in A\}$ is a subring of $S$.

For (1) I have the following: $$ \begin{split} \varphi(na) &= \varphi((n-1)a+a) \\ &= \varphi((n-1)a)+\varphi(a) \\ &= (n-1)\varphi(a)+\varphi(a)\\ &= n\varphi(a). \end{split} $$

For (2): For $n=1$, we have $\varphi(a) = \varphi(a)$. Suppose for some $n\in\mathbb Z^+$ that $\varphi(a^n)=(\varphi(a))^n$. Observe: $$ \begin{split} \varphi(a^n) & =(\varphi(a))^n \\ \varphi(a)\cdot \varphi(a^n) & =\varphi(a)\cdot (\varphi(a))^n \\ \varphi(a \cdot a^n) & =(\varphi(a))^{n+1} \\ \varphi( a^{n+1}) & =(\varphi(a))^{n+1} \\ \end{split} $$

For (3): I verify for $a,b\in\varphi(A)$ then $a-b\in\varphi(A)$ and $a\cdot b\in \varphi(A)$ (for brevity).

  • Well, $0\in A \implies 0 \in \varphi(A) $
  • For $a,b \in \varphi(A)$ we have $\varphi(a) - \varphi(b) = \varphi(a-b)$, thus, verified, because $a-b\in A$.
  • For $a,b \in \varphi(A)$, we have $\varphi(a) \cdot \varphi(b) = \varphi (a\cdot b)$, thus, verified, because $a\cdot b \in A$.

Did I do these right? Feedback appreciated!

$\endgroup$
1
  • 3
    $\begingroup$ Instead of writting "For $n=1$, we have $\varphi(a)=\varphi(a)$" I would write "For $n=1$, we have $\varphi(a^n) = \varphi(a) = (\varphi(a))^n$". $\endgroup$
    – azif00
    Nov 10, 2021 at 17:23

2 Answers 2

6
$\begingroup$

For the first property, use induction to show that $\phi(na) = n\phi(a)$ for all $a$ and $n\geq 0$. This is actually what you have done.

For negative $n$ one must be careful. For $n>0$ put $(-n)a = -(na)$, which is the additive inverse of $na$. This part is then true simply by definition.

$\endgroup$
3
$\begingroup$

I agree with Wuestenfux's answer, and have some feedback to give. There is some error in your answer to part $(1)$, which is similar to one in part $(2)$ as well. How do you know that $\phi((n-1)a)=(n-1)\phi(a)$? For $(2)$ you suppose that there exists some $n\in\mathbb{Z}^+$ satisfies $\phi(a^n) = (\phi(a))^n$, but it could be the case that $\{n\in\mathbb{Z}^+|\phi(a^n) = (\phi(a))^n\}$ is empty. For both $(1)$ and $(2)$, one can use induction after showing the properties hold with base case $n=2$.

For problem $(3)$, remember that if $b = \phi(a)$ for some $a\in A$ then $b\in \phi(A)$. It is only once we write an element $b$ in the form $\phi(a)$ that the containment $b\in \phi(A)$ becomes clear. For example, given $0\in A$, we know by properties of ring homomorphisms that $$\phi(0) =0.$$ Hence $0 = \phi(0) \in \phi(A)$.

"For $a,b\in \phi(A)$, we have $\phi(a) - \phi(b) = \phi(a-b)$." This does not show that $a-b \in \phi(A)$, because $a \neq \phi(a)$ and $b\neq \phi(a)$. Again, to say that $a\in \phi(A)$ means there exists some $x\in A$ for which $\phi(x) = a$.

$\endgroup$
2
  • $\begingroup$ Follow up question, apologies for tardiness. Is the question then supposed to have been for $n\in\mathbb Z^+$ for (1) as well? $\endgroup$
    – Seong
    Nov 11, 2021 at 1:55
  • $\begingroup$ In (1), you can show that the result holds for all $n\in\mathbb{Z}$. A method for doing so is showing that (1) holds for $n\in \mathbb{Z}^+$, then using this to prove that it holds for all $\mathbb{Z}$. See Wuestenfux's answer for more detail. $\endgroup$
    – Matt E.
    Nov 11, 2021 at 19:54

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.